2022
DOI: 10.1186/s41983-022-00486-6
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference between GBS triggered by COVID-19 and those of other origins?

Abstract: Background Since the outbreak of the coronavirus disease 2019 (COVID-19), an increasing number of Guillain–Barré syndrome (GBS) cases following the infection has been reported. The aim of our study was to detect patients with GBS treated in our hospital over a 1-year period and to compare the characteristics and outcomes of those triggered by COVID-19 with the rest of GBS patients. Our prospective study included 29 patients who were diagnosed with GBS from March 2020 to March 2021. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Two patients (0.8%) showed normal electrophysiology. In six cohorts the summed percentage of patients with AIDP was 60.8% in SARS‐CoV‐2 infected patients and 51.8% in non‐infected patients with a non‐significant difference (RR 1.13, 95% CI 0.87; 1.47) (Figure 7a) [9, 28, 45–48]. Axonal GBS (AMAN and AMSAN) was 21.7% in SARS‐CoV‐2 infected and 25.7% in non‐infected patients with a 0.24 times lower risk of axonal GBS in SARS‐CoV‐2 infected patients (RR 0.76, 95% CI 0.56; 1.12) (Figure 7b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two patients (0.8%) showed normal electrophysiology. In six cohorts the summed percentage of patients with AIDP was 60.8% in SARS‐CoV‐2 infected patients and 51.8% in non‐infected patients with a non‐significant difference (RR 1.13, 95% CI 0.87; 1.47) (Figure 7a) [9, 28, 45–48]. Axonal GBS (AMAN and AMSAN) was 21.7% in SARS‐CoV‐2 infected and 25.7% in non‐infected patients with a 0.24 times lower risk of axonal GBS in SARS‐CoV‐2 infected patients (RR 0.76, 95% CI 0.56; 1.12) (Figure 7b).…”
Section: Resultsmentioning
confidence: 99%
“…In four cohorts the raw percentage of cranial nerve involvement was 37.5% in non‐SARS‐CoV‐2 infected patients and 49.1% in SARS‐CoV‐2 infected patients with 1.41 RR of cranial nerve involvement (RR 1.41, 95% CI 1.09; 1.83) (Figure 6c) [9, 28, 45, 46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of our female patient, the first symptoms started 15 days after infection. Radišić et al [ 10 ] showed that there was no difference in clinical and electrophysiological features, disease course, and outcome between post-COVID-19 and non-COVID-19 GBS patients. As for rehabilitation outcomes of post-COVID-19 GBS patients, there are limited data.…”
Section: Discussionmentioning
confidence: 99%
“…Although the experiences of some studies indicate that post-COVID-19, GBS is a more severe in comparison with other post-infective GBS,[ 16 ] our study has not confirmed that. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%